Respuesta :
Answer:
2x2 = 8x-3
4 = 8x - 3 | +3
7=8x
x=7/8
Step-by-step explanation:
Answer:
x = 2 ± [tex]\frac{1}{2}[/tex][tex]\sqrt{10}[/tex]
Step-by-step explanation:
Given a quadratic equation in standard form : ax² + bx + c = 0
Then we can solve for x using the quadratic formula
Given
2x² = 8x - 3 ( subtract 8x - 3 from both sides )
2x² - 8x + 3 = 0 ← in standard form
with a = 2, b = - 8 and c = 3, hence
x = (- (- 8) ± [tex]\sqrt{(-8)^2-(4(2)(3)}[/tex]) / 4
= (8 ± [tex]\sqrt{64-24}[/tex]) / 4
= (8 ± [tex]\sqrt{40}[/tex]) / 4
= (8 ± 2[tex]\sqrt{10}[/tex] ) / 4
= [tex]\frac{8}{4}[/tex] ± [tex]\frac{2\sqrt{10} }{4}[/tex]
= 2 ± [tex]\frac{1}{2}[/tex][tex]\sqrt{10}[/tex]